Socio-Economic Impacts on Livelihood Diversification of Peatland Communities - Pratiwi Subianto; Jonathan Giovanni; Abdul Halim; Suherman Suherman; Tiur Roida Simbolon; M Farras Nasrida (Journal La Sociale, 2026)
This study examines how socioeconomic factors influence livelihood diversification among households living in peatland areas in Palangka Raya City. Peatland ecosystems that are vulnerable to fire, degradation, and environmental pressure require communities to adopt adaptive livelihood strategies to sustain economic stability. Using survey data from 100 households, this study analyzes the roles of education, household income, fire risk, and access to credit within the Sustainable Livelihood Framework. The results show that education and income significantly increase households’ likelihood of diversifying their livelihoods, with education emerging as the most influential factor. In contrast, fire risk and access to credit are not statistically significant. These findings indicate that human capital and internal financial capacity play a more decisive role in livelihood decisions than ecological pressure or financial access alone. The study recommends strengthening education, vocational skills, and peatland-based local economic activities to enhance community resilience and support sustainable peatland development in Palangka Raya.